Pengaruh Struktur Kepemilikan dan Ukuran Perusahaan terhadap Agresivitas Pajak - Ananto Prabowo; Kharisma Dewi; Harsono Yoewono (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2021)
The aim of this research is to examine the impacts of institutional ownership, independent commissioner, and company size on tax aggressiveness. Population of this research are companies that listed in Index Kompas 100 Indonesian Stock Exchange for the year 2014-2018. By using purposive sampling method, 135 companies were selected as samples. The type of data used in this research is secondary data. Meanwhile, the data analysis method that used in this research is descriptive statistics and multiple regression analysis. The analysis showed that institutional ownership has a positive association with tax aggressiveness. While, independent commissioner able at certain level insignificantly able to limit the tax aggressiveness practice. However, firm size affects significantly positive on tax aggressiveness. Further, finding indicates that three variables; Institutional ownership, independent commissioner, and company size together affect the tax aggressiveness.